PARAPROTEINEMIC POLYNEUROPATHY ASSOCIATED WITH MONOCLONAL GAMMOPATHY OF UNDETERMINED SIGNIFICANCE: СLINICAL CASE DESCRIPTION AND LITERATURE REVIEW - A. A. Yakovlev; E. S. Tarabanova; A. G. Smochilin; R. A. Gapeshin; M. V. Yakovleva (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2017)
Monoclonal gammopathy of undetermined significance represents a number of conditions, the development of which is based on functional impairment of B-lymphocytes, which results in permanent pathological secretion of a single clone of immunoglobulins or their constituent chains. One of the leading and often the only clinical manifestation of monoclonal gammopathy is peripheral neuropathy associated with paraproteinemia. The article presents a clinical case of severe peripheral neuropathy associated with monoclonal gammopathy of undetermined significance. The diagnosis was confirmed on the basis of a comprehensive diagnosis, including screening paraproteinemic proteins in serum and a single urine sample is a method of immunofixation. Polyneuropathy was treated by using intravenous human immunoglobulin, as well as non-drug methods of rehabilitation (local cryotherapy, physical therapy and stabilometry). The therapy made a positive effect in reducing the symptoms, primarily the sensory and neuropathic components and polyneuropathy.